2019
DOI: 10.3233/jnd-190428
|View full text |Cite
|
Sign up to set email alerts
|

One Year of Newborn Screening for SMA – Results of a German Pilot Project

Abstract: Objective: Spinal muscular atrophy (SMA) is the most common neurodegenerative disease in childhood. The study was conducted to assess the impact of early detection of SMA by newborn screening (NBS) on the clinical course of the disease. Methods: Screening was performed in two federal states of Germany, Bavaria and North Rhine Westphalia, between January 2018 and February 2019. The incidence in the screening population was calculated as number of detected patients with a homozygous deletion in the SMN1-gene per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0
12

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 126 publications
(130 citation statements)
references
References 52 publications
6
112
0
12
Order By: Relevance
“…The screening procedure has already been published in a previous manuscript, presenting the clinical and electrophysiological outcome after one year of newborn screening for SMA [24]. In short, the screening was performed in two federal states of Germany, Bavaria and North Rhine Westphalia, starting in January 2018.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The screening procedure has already been published in a previous manuscript, presenting the clinical and electrophysiological outcome after one year of newborn screening for SMA [24]. In short, the screening was performed in two federal states of Germany, Bavaria and North Rhine Westphalia, starting in January 2018.…”
Section: Methodsmentioning
confidence: 99%
“…Since a number of SMN-dependent and SMNindependent therapies are available [11], the timing of treatment is crucial for a good outcome [12,13] and available data show that presymptomatic treatment is superior to treatment after onset of symptoms [14] experts agree that newborn screening should be established [15,[16][17][18][19][20][21][22][23]. Currently first pilot projects for a genetic NBS in SMA are underway [18,[24][25][26][27][28]. It has been shown that children with less than 4 SMN2 copies clearly have a benefit from an early presymptomatic treatment [14,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NBS procedure has been published in a previous manuscript 15 . In short, screening was performed in two federal states of Germany, starting in January 2018.…”
Section: Methodsmentioning
confidence: 99%
“…The data analysis software was designed to mask much of the sequence data and reveal only the predetermined CF-causing variants in the CFTR gene as characterized by the CFTR2 project [48,49]. The significance of this study includes: (1) it was the first report from a public health NBS laboratory regarding the technical feasibility of applying NGS in routine NBS practice; and (2) the reported laboratory-developed DNA isolation method in this study is applicable to other molecular testing currently used in public health NBS laboratories, such as multiplexing real-time PCR assays to screen for severe combined immunodeficiency (SCID) [50] and spinal muscular atrophy (SMA) [51,52].…”
Section: Application Of Next Generation Sequencingmentioning
confidence: 99%